Developing edutourism satisfaction index: religiosity and spirituality embedded model in the selection of a destination for edutourism - Osman-Gani, AAhad M.; Mat Daud, Nuraihan; Hasliza Hassan, Hassan; Raman, Murali; Abdul Latif @ Bapoo, Lilisuriani; Rahman, Muhammad Sabbir (2019)
The purpose of this research is to empirically examine the critical factors that influence international students’ perceptions in the selection of a destination for educational tourism. This research seeks to develop a framework embedded with service quality, destination image and spirituality behavior. The data were collected by using a self-administered questionnaire to a sample of 220 respondents who were studying at the universities in Peninsular Malaysia. The constructs and items used in the questionnaire were adapted from the previously used validated research instruments identified through literature reviews. This research applied confirmatory factor analysis and structural equation modeling to test the proposed hypotheses. The results indicated that there is a significant relationship between service quality and the choice of a destination for educational tourism. This research also identified that destination brand image significantly relates to the selection of a destination for educational tourism when the destination loyalty plays a strong mediation role. Interestingly, the direct relationship between spirituality behavior and selection of destination was not found to be significant. On the other hand, a significant relationship was discovered between spirituality behavior and choice of destination when the tourists’ intention plays as a mediating function.